Evaluation of Anti-inflammatory and Antioxidant Effects of Sumatriptan on Carbon Tetrachloride-induced Hepatotoxicity in Rats - Dehpour, Ahmad Reza; Yousefi-Manesh, Hasan; Sheibani, Mohammad; Sadeghi, Mohammad Amin; Hemmati, Sara; Noori, Tayebeh; Shirooie, Samira (Drug Research, 2021)
The liver detoxifies and metabolizes many drugs and xenobiotics which may cause hepatotoxicity due to some toxic agents. Carbon tetrachloride (CCl4) is metabolized in cytochrome P450 and its reactive radical metabolites cause lipid peroxidation, cellular injury, and apoptosis. Sumatriptan (SUM), 5-HT1B/1D receptor agonist, had anti-inflammatory and anti-oxidant effects. In this research the effect of SUM pre-treatment against CCl4-induced hepatotoxicity was examined. Adult rats received SUM (0.1, 0.3 and 1 mg/kg; i.p.) for 3 consecutive days before CCl4 (2 ml/kg; i.p. on the 3rd day). The aminotransferases serum levels, tissue levels of anti-oxidant and pro-inflammatory markers and histopathological examination were evaluated. SUM (0.3 mg/kg) prevented significantly the elevation of aminotransferases versus the control group (CCl4 group) (P<0.0001) and also, reversed meaningfully the changes of the MPO, MDA, SOD and CAT, IL-1β and TNF-α levels. Additionally, CCl4-intoxication resulted to the disruption of lobular and cellular structures and inflammation in histopathological evaluation which is prevented by SUM (0.3 mg/kg). These data revealed that SUM (0.3 mg/kg), but no at doses 0.1 and 1 mg/kg, decreases the hepatotoxicity of induced by CCl4 in rats.
Keywords: CCl4; Hepatotoxicity; Sumatriptan; Inflammation; Oxidative stress